The four philosophies of lean : maintaining a customer-focused culture every day at work - Corbitt, Robert; Bronger, Cory (Productivity Press, 2021)
This book provides a comprehensive look at four driving philosophies of Lean methodology that many companies struggle to understand. Companies often adopt Lean methodologies and work hard to perfect the use of those methods while never understanding the true intent of the method. Ultimately, knowledge does not equal understanding. "Customer First" is about each manufacturing process sending the next manufacturing process a high-quality defect-free product every time. When people hear the word "Customer" their mindset is thinking about the end user, but when a company understands every process has a Customer a high- quality product is produced at each stage of the manufacturing process. As kids most of us grew up hearing the phrase "respect your elders," and while this still applies, respect for people has additional and stronger connotations. In business, the work content must fit the capacity -- in lay terms, a fair day's work for a fair day wage. Setting up our colleagues for failure by giving them more work content than can be completed is not showing them respect, and in essence, it is simply disrespectful. In addition, respect is how we develop and engage our colleagues in their daily work. "Go and See" is often overlooked because we know the process in which the problem exists, but if we evaluate what is actually happing you generally find that what "should be" happening is not happening. As people view what is happening, questions will come to mind: How does the operator know to do that? Does the standard work give that knowledge? These questions lead to giving clarity about the problem and will drive the thinking to a solution. Business in general is dynamic and ever changing. Companies must be able to adapt, overcome, and improvise to remain competitive. The challenge is identifying where to target or how to develop a continuous improvement culture in the workforce to drive improvement. Companies get stuck in the mindset of "this is how we have always done it" and this mindset can be a very limiting or even crippling situation